Microbial assessment of different samples of ostrich (Struthio camelus) and determination of antimicrobial susceptibility profiles of the isolated bacteria (Asian Journal of Medical and Biological Research, 2018)
The study was conducted to monitor the microbial assessment in oropharyngeal swab, cloacal swab and faecal samples of ostrich and also update knowledge on antimicrobial sensitivity of isolated organisms. The study was performed at Hajee Mohammad Danesh Science & Technology University (HSTU) ostrich farm from January to June, 2016. A total 75 samples were randomly collected from 8 ostriches at different age of which 25 oropharyngeal, 25 cloacal swabs sample and 25 were faeces samples. The organisms were isolated by using standard microbiological method. The result revealed that the average microbial load in plate count agar was highest in faeces (1.48×109±0.27 CFU) than oropharyngeal swab (1.36×109±0.38 CFU) and cloacal swab (1.28×109±0.34 CFU). Among 75 samples, 29 (38.66%) Escherichia coli, 21 (28%) Salmonella spp., 20 (26.67%) Staphylococcus spp. and 5(6.6%) Bacillus spp. were identified. In 25 oropharyngeal swab samples, Staphylococcus spp. was found highest 15 (60%) than other organisms but Escherichia coli were found highest both in cloacal 11(44%) and faecal 12(48%) samples. On antibiogram study Escherichia coli, Salmonella spp., Staphylococcus spp. and Bacillus spp. were more sensitive to Levofloxacin, Azithromycin, Nalidixic Acid and Amoxicillin respectively. While more resistant to Azithromycin, Penicillin, Chloramphenicol and Erythromycin respectively. The obtained results indicated that ostrich excreta are one of the most important sources of Escherichia coli, Staphylococcus spp., Salmonella spp., Bacillus spp. in ostrich farms. Finally, it may be concluding that the logical use of antibiotics must be adopted in ostrich farms reared in Bangladesh for prevention of the appearance of multidrug resistance bacteria. Moreover, proper measures should be taken to aware off zoonotic diseases in peoples who are involved in ostrich farming.Asian J. Med. Biol. Res. December 2017, 3(4): 437-445